The Routledge handbook of critical social work pedagogies - Morley, Christine; Morley, Christine (London Routledge, 2020)
"The handbook traverses new territory by providing a cutting-edge overview of the work of classic and contemporary theorists, in a way that expands their application and utility in social work education and practice; thus, providing a bridge between critical theory, philosophy, and social work. It will be instructive for social work educators who aim to teach for social change, and hold relevance for both postgraduate and undergraduate/qualifying social work and human services courses around the world"--
Includes bibliographical references and index.
Keywords: Social work education; Social service; Critical theory